Structure and Dynamics of Granular Materials Perturbed by External Fields - Gerasymov, O.I. (Український фізичний журнал, 2010)
The problem of the description of a local structure of granular materials is discussed within the concept of existence of structural invariants. The superimposition of this approach with the probabilistic arguments concerning the crossover to the kinetics of a transition between states with different measures gives a relevant picture of the evolution with a reminiscence of the first-order phase transition between states with different structural orderings. Проблема опису локальної структури гранульованих матерiалiв запропонована до розгляду з концепцiєю iснування структурних iнварiантiв. Доповнений iмовiрнiсним сценарiєм переходiв мiж квазiстацiонарними станами пiдхiд дає можливiсть опису зв’язкiв мiж параметрами локальної структури у виглядi iнварiантiв з кiнетикою змiн станiв впорядкування, що має ознаки фазових перетворень першого роду.